Agriculture Supply Chain Management Based on Blockchain Architecture and Smart Contracts. (21st October 2022) - El Mane, Adil; Chihab, Younes; Tatane, Khalid; Korchiyne, Redouan
Abstract : Since the commercialization of agriculture technology, there has been a surge in interest in agricultural data. However, these data are notoriously chaotic, and analysts are concerned about their authenticity because there is a big possibility that others may have influenced data quality at various points along the data stream. This article suggests a new blockchain architecture to protect the integrity of agricultural data. The goal of this architecture is to provide farmers with safe storage. The agriculture data inserted cannot be modified without some rules. Many procedures are completed automatically using smart contracts to limit the danger of manipulation. One of the suggested architectures is the proof of concept. It connects a traditional farm system with the blockchain accompanied by smart contracts to facilitate the entire agri-supply chain. The conceptual architecture will eliminate the flaws discovered in prior studies. Sensors are used in this approach to provide us with environmental data. As a result, we store our data in blocks using the blockchain system. Then, we built some unique agricultural smart contracts to handle all transactions and automatize decisions based on the source code of these automated contracts. This strategy would be more efficient and secure.